2020
DOI: 10.5194/angeo-38-953-2020
|View full text |Cite
|
Sign up to set email alerts
|

Semiannual variation of Pc5 ultra-low frequency (ULF) waves and relativistic electrons over two solar cycles of observations: comparison with predictions of the classical hypotheses

Abstract: Abstract. Pc5 ULF (ultra-low frequency) waves can energize electrons to relativistic energies of >2 MeV in geostationary orbits. Enhanced fluxes of such electrons can induce operational anomalies in geostationary satellites. The variations of the two quantities in timescales ranging from days to solar cycles are thus of interest in gauging their space weather effects over different time frames. In this study, we present a statistical analysis of two 11-year solar cycles (cycles 22 and 23) of data comprising… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…There are, nonetheless, two other mechanisms proposed to explain SAV (e.g. Poblet, Azpilicueta, and Lam, 2020;Lockwood et al, 2020): the axial hypothesis, that states the main cause is the position of the Earth with respect to the solar equator (the heliographic latitude), with maximum near the equinoxes Figure 8. The θ RM during the spring equinox, with IMF toward the Sun.…”
Section: Analysis Of 27-day-mean Series Of Asymmetriesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are, nonetheless, two other mechanisms proposed to explain SAV (e.g. Poblet, Azpilicueta, and Lam, 2020;Lockwood et al, 2020): the axial hypothesis, that states the main cause is the position of the Earth with respect to the solar equator (the heliographic latitude), with maximum near the equinoxes Figure 8. The θ RM during the spring equinox, with IMF toward the Sun.…”
Section: Analysis Of 27-day-mean Series Of Asymmetriesmentioning
confidence: 99%
“…There are, nonetheless, two other mechanisms proposed to explain SAV (e.g. Poblet, Azpilicueta, and Lam, 2020;Lockwood et al, 2020): the axial hypothesis, that states the main cause is the position of the Earth with respect to the solar equator (the heliographic latitude), with maximum near the equinoxes (±7.5 o ) and minimum near solstices (∼ 0 o ); the equinoctial hypothesis, that identifies as the most relevant parameter the angle between the Earth-Sun line and the geomagnetic dipole axis of the Earth (the tilt angle, or its complement). Zhao and Zong (2012) noticed that, if R-M is the dominant mechanism behind SAV, a toward/away asymmetry should be seen in geomagnetic activity.…”
Section: Analysis Of 27-day-mean Series Of Asymmetriesmentioning
confidence: 99%
“…There are, nonetheless, two other mechanisms proposed to explain SAV (e.g. Poblet, Azpilicueta, and Lam, 2020;Lockwood et al, 2020): the axial hypothesis, that states the main cause is the position of the Earth with respect to the solar equator (the heliographic latitude), with maximum near the equinoxes (±7.5 o ) and minimum near solstices (∼ 0 o ); the equinoctial hypothesis, that identifies as the most relevant parameter the angle between the Earth-Sun line and the geomagnetic dipole axis of the Earth (the tilt angle, or its complement).…”
Section: Analysis Of 27-day-mean Series Of Asymmetriesmentioning
confidence: 99%
“…Furthermore, Emery et al (2011) used > 2 MeV electron fluxes from Geostationary Operational Environmental Satellite (GOES) and argued that the SAV, which was relatively strong in the 1995-1997 solar minimum, was a combination of the Russell-McPherron effect and the appearance of equinoctial peaks in the amplitudes of solar rotation periods of 13.5 and 27 d. Finally, Poblet et al (2020) used GOES > 2 MeV electron fluxes during the 1987-2008 time period and concluded that the equinoctial mechanism seems to be the dominant driver of the SAV of electron fluence at GEO.…”
Section: Introductionmentioning
confidence: 99%